1972
DOI: 10.1007/bf01373466
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of banding nitrogen fertilizers in soil

Abstract: SUMMARYAn account is given of the iilteractions which occur when urea or ammonium sulphate is banded in a clay soil. The spatial distribiltions of ammonium, nitrate, and nitrite around the band are given as functions of time and are discussed in relation to results from a series of Jncubations of homogeneous mixtures of various nitrogen compounds and soll. The ditIusion of the banded fertilizers and their products throilgh the soil presents the nitrifying organisms with a wide range of environments. The patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…The reason for this effect is not clear. Fertilizer banding is known to inhibit nitrification (Wetselaar et al 1972). Despite this inhibition, soil nitrate concentrations were higher for the S150 treatment than for the S75 treatment, and there was limited evidence that N 2 O emissions were nitrate limited; therefore, the reduced N 2 O emissions for the S150 treatment cannot be attributed to a reduced nitrate supply as a result of inhibition of nitrification.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reason for this effect is not clear. Fertilizer banding is known to inhibit nitrification (Wetselaar et al 1972). Despite this inhibition, soil nitrate concentrations were higher for the S150 treatment than for the S75 treatment, and there was limited evidence that N 2 O emissions were nitrate limited; therefore, the reduced N 2 O emissions for the S150 treatment cannot be attributed to a reduced nitrate supply as a result of inhibition of nitrification.…”
Section: Discussionmentioning
confidence: 98%
“…This primarily reflects the delay in fertilizer N application for the S150 treatment, but also likely reflects the difference in application method (broadcast vs. band). Banding of fertilizer N inhibits the nitrification process (Wetselaar et al 1972), and elevated soil NH 4 -N concentrations have been reported to persist after fertilizer banding (Zebarth et al 1999). Sidedress application of fertilizer N at the six-leaf stage is, therefore, an effective means of reducing nitrate intensity in corn production, even if the same rate of fertilizer N is applied.…”
Section: Discussionmentioning
confidence: 99%
“…137 Bezdicek et al13= compared the behaviour of urea, diammonium phosphate and ammonium sulfate in an alkaline soil. They found that the highest accumulation of nitrite (260ppm) occurred in the soil to which urea had been added.…”
Section: Accumulation Of Nitritementioning
confidence: 99%
“…4). Wetselaar et al (1972) found that nitrification was inhibited when soil ammonium-N concentrations exceeded 3000 mg N kg -1 soil under near neutral soil pH values. Assuming a soil pH of 7, and similar conditions as in Fig.…”
Section: Resultsmentioning
confidence: 98%